Case-Control Study of the Effects of Gut Microbiota Composition on Neurotransmitter Metabolic Pathways in Children With Attention Deficit Hyperactivity Disorder - Wan, Lin; Ge, Wen-Rong; Zhang, Shan; Sun, Yu-Lin; Wang, Bin; Yang, Guang (Frontiers in Neuroscience, 2020)
Abstract Background: Attention-deficit/hyperactivity disorder (ADHD) is a neuropsychiatric condition that may be related to an imbalance of neural transmitters. The gut microbiota is the largest ecosystem in the human body, and the brain-gut axis theory proposes that the gut microbiome can affect brain function in multiple ways. The purpose of this study was to explore the gut microbiota in children with ADHD and assess the possible role of the gut microbiota in disease pathogenesis to open new avenues for ADHD treatment. Methods: A case-control design was used. We enrolled 17 children aged 6–12 years with ADHD who were treated in the Pediatric Outpatient Department of the First Medical Center of the Chinese PLA General Hospital from January to June 2019. Seventeen children aged 6–12 years were selected as the healthy control (HC) group. Fecal samples of cases and controls were analyzed by shotgun metagenomics sequencing. Alpha diversity and the differences in the relative abundances of bacteria were compared between the two groups. Functional annotations were performed for the microbiota genes, and metabolic pathways were analyzed using the Kyoto Encyclopedia of Genes and Genomes. Results: There was no significant difference in the alpha diversity of gut microbiota between the ADHD and HC groups. Compared with HCs, Faecalibacterium and Veillonellaceae were significantly reduced in children with ADHD (P<0.05), Odoribacter and Enterococcus were significantly increased (linear discriminant analysis>2). At the species level, Faecalibacterium prausnitzii, Lachnospiraceae bacterium, and Ruminococcus gnavus were significantly reduced in the ADHD group (P<0.05), while Bacteroides caccae, Odoribacter splanchnicus, Paraprevotella xylaniphila, and Veillonella parvula were increased (P<0.05). Metabolic pathway analysis revealed significant between-group differences in the metabolic pathways of neurotransmitters (e.g., serotonin and dopamine) (P<0.05). Conclusions: Composition differences of gut microbiota in subjects with ADHD may contribute to brain-gut axis alterations and affect neurotransmitter levels, which could contribute to ADHD symptoms.